Revolution and Growth of Food Service Industry - The impact of Food-Tech Start ups - Singh, Charanjot; Sharma , Zeenia (Gyan Management Journal, 2018)
The dawn of the millennium may not have foreseen the change in the way most businesses operate, as we see today. An internet user base of nearly 40% of India's population and the extensive involvement of Information Technology in the retail sector has resulted in a fundamental shift in the behaviour and practices of both, consumers and sellers. This led to an accelerated growth across various industries, making room for more development, by offering convenience and variety to the consumer, as is the case with the Food Service Industry in India. The Indian food service industry is one of the fastest evolving industries, owing to changing demographics, increase in disposable income, urbanization and effective operating models. The involvement of new Internet-based intermediaries has played a major role in organizing the previously unorganized industry. The advancement in technology and emerging retail formats have given rise to novel business ideas and platforms catering to the dynamic needs of the modern consumer, empowering them by giving them the freedom to make informed decisions, and at the same time, giving a wider outreach to the sellers. The undertaken research aims at studying the quantified effect of digitization on the growth of businesses, as reported by the merchants in the organized food service industry in Chandigarh. The study was conducted based on responses collected from the managers of restaurants and cafes that have been using Zomato as an additional platform for conducting business for over a year.
Keywords: Digitization; Food-tech startups; Food service industry; Zomato